"Of All the Social Workers ... I'm the Bad One": Impact of Disciplinary Action on Social Workers. (1st October 2018) - Gricus, Michelle
Abstract: The Code of Ethics of the National Association of Social Workers makes several professional responsibilities clear; however, no explicit duty exists to restore dignity and reintegrate a social worker who has been reported to the licensing board for engaging in unethical or unprofessional behavior. This article, which reports the qualitative results of a mixed methods study, examines the personal and professional effects of disciplinary action on those social workers who have been sanctioned by a state board of social work. Through a symbolic interactionist lens, the author interviewed 18 social workers who had been disciplined by their licensing board and found that participants were often notably affected by the experience. The themes in the findings involved negative psychological and personal impacts, long-term vocational concerns, poor treatment by the board, and the importance of support to endure the experience. A notable social work implication includes generating clearer responsibilities for social workers around rehabilitation of those who have been disciplined.